Migrazioni "forzate": Un episo dio di captivitas nella Puglia del primo ottocento - Attanasio, Francescapia (Vergentis, 2020)
Some papers kept in the Foggia State Archive reveal a little-known cross-section of the migratory phenomenon between the two southern shores of the Adriatic in the early nineteenth century. It consisted in the mutual displacement of "foreigners" who reached the coasts of the Kingdom of the Two Sicilies and depleted then inhabitants to be used, in all probability, for slave duties. One of the most striking episodes of aggression was recorded in Monte S. Angelo in 1804, when a group of unfortunates was captured by unidentified foreigners. The story can be reconstructed thanks to a series of documents, including the declaration made by the prefect of Lucera who intended to initiate, by faith of slavery, the procedure for their freedom. The expulsive phenomenon, which therefore did not stop at the old regime but persisted even after the Enlightenment claim of fundamental rights, deserves to be reconstructed with particular regard to the historical-juridical implications: it generated - still in the 19th century - serious consequences of public order, which deeply affected the southern society, its perception of insecurity, trust feelings between population and institutions.